Multiple Possible Causes Of Dyspnea In An Unusual Pickwickian Syndrome On Covid-19 Pandemic: A Case Study - Steven Jonathan; Menaldi Rasmin (Respiratory Science, 2022)
Introduction: Pickwickian Syndrome (PS) or obesity hypoventilation syndrome (OHS) is a diagnosis of exclusion with features of obesity, sleep disordered breathing, and chronic daytime hypercapnia. Patients with PS could present into general OSA or respiratory failure. We are presenting an unusual case of PS with acute respiratory failure resulting in organ failure and mortality. Case report: A 41-year-old male was admitted to hospital due to shortness of breath. He had a trouble sleeping; frequently awoke as the breathing briefly stopped and gasping. There were history of diabetes melitus (DM) and hypertension for >10 years, smoking with moderate Brinkman Index. Patient appeared to have somnolence, tachypnea, hypoxemia, morbid obesity. We assessed him as PS, bronchopneumonia, respiratory failure, pulmonary edema, hypertensive heart disease (HHD), DM, acute on CKD. We managed him with pharmacotherapy, oxygen (BiPAP), and hemodialysis. After transferred from ICU to regular ward, patient was suddenly apneic and CPR was performed; ended in mortality. Discussion: This unusual case (malignant OHS) was a subgroup among OHS with greater morbidity and multiorgan system dysfunction. There were multiple causes of dyspnea on our patient which concluded to a death case. There are three modalities of management in stable PS: positive airway pressure (PAP), weight reduction, and pharmacotherapy. The management of respiratory failure in PS mainly involved oxygen therapy in positive pressure. Conclusion: There were multiple causes of dyspnea in this patient. Optimal management of patient ought to treat not only the PS but also all the comorbidities.